Perbandingan Algoritma Pengkodean Suara Manusia : Adaptive Delta Modulation and Linear Prediction Coding - Djadjat Sudaradjat (LPPM Universitas Bina Sarana Informatika, 2019)
Coding algorithms human voice with ADM (Adaptive Delta Modulation) and LPC (Linear Prediction Coding) made to the encoding signals digitally produced has bit rate as low as possible, thus saving bandwidth transmission line if it will be distributed to the transmission medium, and save memory or computer storage if it will be stored as data storage.ADM technique different from the LPC, the difference is generally classified on how it is encoded. If the ADM system which is encoded representation of the waveform so often called